S2A:6 Soluble urokinase plasminogen activator receptor (supar) predicts the development of organ damage over 5 years in systemic lupus erythematosus: results from the slicc inception cohort. (21st March 2018) - Enocsson, H; Wirestam, L; Wetterö, J; Skogh, T; Bruce, IN; Sjöwall, C
Abstract : Background: The urokinase plasminogen activator receptor (suPAR) participates in proteolysis, migration and adhesion. Receptor shedding yields a soluble form (suPAR) that has emerged as a promising severity biomarker in malignancies, inflammatory and infectious diseases. Previously, suPAR was shown to reflect accumulated organ damage in systemic lupus erythematosus (SLE). Here, we investigate suPAR as a potential predictor of future organ damage in patients with recent-onset SLE. Methods: 345 SLE cases (at least 4 ACR criteria) from North America, Europe and Asia were included. All patients were from the SLICC inception cohort and were selected based on a minimum of 5 years follow-up and absence of organ damage (SLICC/ACR damage index; SDI>0) at inclusion. Patients were enrolled within 15 months of diagnosis. Estimated glomerular filtration rate (eGFR) was available for 180 patients. Serum suPAR levels were measured by ELISA at inclusion only, and levels were related to SDI after 5 years of follow-up. Age- and sex-matched controls (1:1) were from the Swedish population. Results: Baseline suPAR levels were higher in patients who acquired damage (SDI>1) over a 5 year period (n=33) compared to patients without damage development (n=246; p<0.001) and controls (n=345; p=0.007) (figure 1). There were no significant differences in suPAR with regard to ethnicity (Caucasians vs non-Caucasians) or sex in patients/controls, but a weak correlation between age and suPAR among controls (p<0.001, r=0.23). No correlations (r>0.2) were found between suPAR and disease activity (SLEDAI-2K), corticosteroid dose or eGFR. Logistic regression revealed significant impact of baseline suPAR on future damage (SDI>1) (p=0.014; area under curve, AUC=0.64) and the predictive value became stronger after adjustment for age, sex, ethnicity and corticosteroid dose (p=0.008; AUC=0.74). Examining individual components of SDI revealed significant impact of suPAR on musculoskeletal damage (SDI>0) (p=0.018; AUC=0.66) lso when adjusting for covariates (p=0.020; AUC=0.68). Conclusion: Prognostic biomarkers of disease severity in SLE could identify patients in need of tight control and improved treatment strategies. Here, suPAR is for the first time shown to have predictive potential of damage accrual in SLE. Continued follow-up of patients could elucidate the association between suPAR and damage in specific organ domains.